2017
DOI: 10.1177/0961203317734922
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial-induced cardiomyopathy: a systematic review of the literature

Abstract: Background Antimalarials (AMs) are widely used in the treatment of connective tissue diseases. Their main side effect is retinal damage, while heart disease has been described in isolated cases. The aim of this study is to systematically review the existing literature on AM-induced cardiomyopathy (AMIC). Methods The PubMed database was searched for heart biopsy-confirmed AMIC cases. Information on demographics, clinical presentation, concomitant AM-related toxicity, cardiological investigations, treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 53 publications
(174 reference statements)
3
69
0
5
Order By: Relevance
“…A 2015 review of the literature and a prospective study demonstrated that the incidence of clinically significant valvular heart disease is low in the absence of a murmur in these category of patients, so in this review they suggest to screen these patients only by physical examination and echocardiogram should be reserved to patients with audible murmur as in our case and those treated for more than 5 years at high doses of cabergoline. [12] Moreover, drug induced valvulopathy is a condition that includes changes in the functionality and morphology of the valves with thickening and restriction [13,14]. The differential diagnosis is difficult, but specific echocardiographic pattern are needed to lead the way.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 review of the literature and a prospective study demonstrated that the incidence of clinically significant valvular heart disease is low in the absence of a murmur in these category of patients, so in this review they suggest to screen these patients only by physical examination and echocardiogram should be reserved to patients with audible murmur as in our case and those treated for more than 5 years at high doses of cabergoline. [12] Moreover, drug induced valvulopathy is a condition that includes changes in the functionality and morphology of the valves with thickening and restriction [13,14]. The differential diagnosis is difficult, but specific echocardiographic pattern are needed to lead the way.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some rare but severe complications may occur such as anti-malarial myopathy or cardiomyopathy and antimalarial maculopathy. 73 Among the two available anti-malarial drugs, HCQ is the one with the lowest retinal toxicity. 74 Azathioprine AZA is a prodrug converted in vivo into its active metabolite, 6-mercaptopurine.…”
Section: Antimalarial Drugsmentioning
confidence: 99%
“…In this issue of The Journal, Tselios, et al 6a , report from their cohort the diagnosis, disease course, and outcome of 8 patients with antimalarial-induced cardiomyopathy, an underrecognized complication that has been reported with longterm use and higher cumulative doses of chloroquine and HCQ 7 . To better understand the risks posed by this case series, we must first review the biological pharmacology and pharmacodynamics of HCQ.…”
Section: Hydroxychloroquine -How Much Is Too Much?mentioning
confidence: 99%